ANALISIS SENSITIVITAS DAN SWITCHING VALUE USAHA BUMBU SERBUK BAWANG PUTIH (Allium sativum L.) DI PT GINTEANC SARI ROSO - Dera Dewi Saputri; Fitria Naimatu Sadiyah; Ananti Yekti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aims to analyze the financial feasibility, sensitivity levels, and feasibility thresholds of the garlic powder (Allium sativum L.) business at PT Ginteanc Sari Roso in response to changes in production volume and sales volume. As this business is relatively new, the analysis was conducted using a five-year cash flow projection based on the assumption of gradual production growth of 25–30%. The methods used include financial feasibility analysis using the Net Present Value (NPV), Gross B/C, Net B/C, Internal Rate of Return (IRR), and Profitability Index (PI) indicators, as well as sensitivity analysis and switching value analysis. The research results indicate that the business is financially viable with an NPV of Rp16,815,876.22; Gross B/C of 1.44; Net B/C of 6.27; IRR of 122.16%; and PI of 3.79. The sensitivity analysis results show that sales volume is more sensitive to the business’s financial viability than production volume. The switching value analysis indicates a tolerance limit for a decrease in production volume of 78.27%, while the tolerance limit for sales volume is 31.46%. These findings indicate that the financial feasibility of the business is more sensitive to changes in sales volume than to changes in production volume. The tolerance limit information obtained through the switching value analysis can be used as a basis for risk control and business decision-making.